Jerusalem : One City, Three Faiths - Armstrong, Karen, 1944- (New York Ballanttine Books, 2005)
This companion to History of God explores the history of Jerusalem as a holy city for Jews, Christians, and Muslims. Examines the myth and symbolism of a transcendent "sacred place," where believers can reconcile with God. Laments the absence of charity and social justice in the city's tumultuous past.
Include Notes, Bibliography and Index
Keywords: Jerusalem -- Ethnic relations -- Jerusalem -- Religion -- Jerusalem -- History